2021
DOI: 10.1158/0008-5472.can-20-0782
|View full text |Cite
|
Sign up to set email alerts
|

E7386, a Selective Inhibitor of the Interaction between β-Catenin and CBP, Exerts Antitumor Activity in Tumor Models with Activated Canonical Wnt Signaling

Abstract: The Wnt/β-catenin signaling pathway plays crucial roles in embryonic development and the development of multiple types of cancer, and its aberrant activation provides cancer cells with escape mechanisms from immune checkpoint inhibitors. E7386, an orally active selective inhibitor of the interaction between β-catenin and CREB binding protein, which is part of the Wnt/β-catenin signaling pathway, disrupts the Wnt/β-catenin signaling pathway in HEK293 and adenomatous polyposis coli (APC)-mutated human gastric ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 50 publications
(32 reference statements)
0
25
0
Order By: Relevance
“…Similarly, the non-responders to anti-PD-1 therapy in our cohort also demonstrated an enriched Wnt/β-catenin pathway. Recently, a selective inhibitor of the interaction between β-catenin and CREB binding protein demonstrated synergistic antitumor activity in combination with PD-1 blockade via modulation of the Wnt/β-catenin pathway and alteration of the tumor immune microenvironments in vivo (27,28). Thus, ICI resistance in MSI-H/dMMR GI tumors can potentially be overcome by targeting the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the non-responders to anti-PD-1 therapy in our cohort also demonstrated an enriched Wnt/β-catenin pathway. Recently, a selective inhibitor of the interaction between β-catenin and CREB binding protein demonstrated synergistic antitumor activity in combination with PD-1 blockade via modulation of the Wnt/β-catenin pathway and alteration of the tumor immune microenvironments in vivo (27,28). Thus, ICI resistance in MSI-H/dMMR GI tumors can potentially be overcome by targeting the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, abnormal expression of p53 functions as a transcription factor that directly activates the expression of relevant genes in immune cells, thus regulating the proliferation of tumor cells; On the other hand, it can be used as tumor-associated antigen to stimulate an immune response. Studies have shown that abnormal expression of the Wnt signaling may also disrupt tumor immunodetection and promote tumor immune evasion ( 76 ). MAPK signal transduction inhibits the activity of immune cells in the TME by upregulating the release of cytokines such as IL-6 and IL-10 ( 77 ).…”
Section: Jmjd6 Regulates the Innate Immune Responsementioning
confidence: 99%
“…In a phase I clinical study, for example, PRI-724, an inhibitor of the β-catenin interaction with the transcriptional coactivator cyclic AMP response element-binding protein (CBP), converted eight patients (40%) into stable disease with a median progression-free survival (PFS) of two months [44]. Another antagonist of the β-catenin-CBP complex, E7386, significantly attenuated Wnt signaling in patient-derived hepatocellular carcinoma (HCC) xenograft models, and is being tested in early phase clinical studies [45]. Besides, antagonistic antibodies of Frizzled receptors, such as Vantictumab and Lpafricept, and anti-ROR1 antibody Cirmtuzumab are still in phase I trials without convincing outcomes [46][47][48][49][50][51].…”
Section: Targeting Wnt Pathway With Rnai Therapeuticsmentioning
confidence: 99%